Analysis of community readiness in the process of revitalizing tourism villages: a case study of Sidoharjo Tourism Village, Yogyakarta - Rina Widiastuti; Nuryuda Irdana; Bima Andi Gunawan; Mutiara Maulida Purnaningtyas (Universitas Merdeka Malang, 2023)
Rural tourism has become an alternative concept trend in rural economic development in Indonesia in the last decade. Tourism in rural areas is a business sector expected to improve the economy of rural communities, one of which is in the Sidoharjo Tourism Village located in Kulon Regency, Yogyakarta Special Region Province. According to data from the Tourism Village Network of the Ministry of Tourism and Creative Economy, Sidoharjo Tourism Village is a tourism village with a developing category because of its diverse attractions. However, initial observations show that Sidoharjo as a tourism village product has not fully fulfilled the elements of developing a tourism village ecosystem with a developing category listed in the 2021 Tourism Village Guidelines. Therefore, the revitalization of the Sidoharjo Tourism Village is significant. For that, we need to analyze the readiness of the tourism village ecosystem to support revitalization with the Community Readiness Model approach. Data collection techniques using semi-structured interviews, observation, and literature study. The study's results revealed that the people of Sidoharjo were in the pre-planning stage. This result shows that the residents of Sidoharjo are not ready to support the revitalization of the Sidoharjo Tourism Village into an advanced tourist village. The analysis results also reveal that the tourism village category developed by the government version does not match the facts at the research location. Sidoharjo Tourism Village has returned to being a tourism village in the pioneer category due to the stagnation in the development of tourism products.Â